Influence of the addition of glass fibers reinforcements in the flexural strength of acrylic resin - Possari, João Gabriel Ezequiel; Sacorague, Samia Carolina Mota; Feitosa, Fernanda Alves; Penteado, Marcela Moreira; Sichi, Luigi Giovanni Bernardo; De Araújo, Rodrigo Máximo (Brazilian Dental Science, 2020)
Objective: To evaluate the influence of glass fiber reinforcements used in nautical and sports products on the flexural strength of acrylic resin. Materials and methods: Thirty thermoactivated acrylic resin bars (25 x 10.5 x 3.3 mm) were used. The samples were shared in 3 groups: bars with no glass fiber (control group, n = 10), bars reinforced with glass fiber and 0.18 mm thickness (group F1, n = 10) and bars reinforced with glass fiber and 0.80 mm thickness (group F2, n = 10). After 48 hours, samples were submitted to compression test in order to evaluate flexural strength. Obtained data were statistically analyzed with significance level of 5 %. Results: It was observed that the use of glass fiber effectively increased the flexural strength compared to the control group; the thickness of the glass fiber, however, did not present statistical differences. Conclusion: The use of fiber glass is a simple and cost-effective alternative to improve acrylic resin performance.KeywordsFlexural strength; Water sports; Dentures.